PRINCIPLES OF STATE REGULATION FINANCIAL SERVICES MARKET OF UKRAINE - V. Shpachuk; T. Bezverkhniuk; V. Vyshnevska; I. Sencha; V. Zalizniuk (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article reveals the main features of the financial services market and its regulation by the state. The analysis of factors influencing the formation of the system of state regulation and infrastructure of the financial services market of Ukraine is carried out, the current state of the system of state regulation of the financial services market of Ukraine is characterized. The periodization of the evolution of the formation and development of the system of state regulation of the domestic financial services market has been carried out. The results of this study suggest that ensuring the greatest efficiency of the system of state regulation of the domestic financial services market is possible through the comprehensive implementation of a number of measures and actions. In particular, a set of measures is proposed, which takes into account the factors influencing the formation and formation of the system of state regulation of the financial services market, the most pressing problems of the financial services market, strategic priorities for further development of the domestic financial services market regulation system. At the same time, it is established that the priority should be to strengthen the institutional capacity of state financial institutions, increase the level of transparency of their activities, as well as increase the functional efficiency of the financial services market regulation system.